2014
DOI: 10.5194/esd-5-441-2014
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting roles of interception and transpiration in the hydrological cycle – Part 1: Temporal characteristics over land

Abstract: Abstract. Moisture recycling, the contribution of terrestrial evaporation to precipitation, has important implications for both water and land management. Although terrestrial evaporation consists of different fluxes (i.e. transpiration, vegetation interception, floor interception, soil moisture evaporation, and open-water evaporation), moisture recycling (terrestrial evaporation-precipitation feedback) studies have up to now only analysed their combined total. This paper constitutes the first of two companion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 107 publications
13
139
2
Order By: Relevance
“…2); however, the contribution from these areas to the global volumes is rather marginal (< 5 % based on our analyses). For comparison, values typically found in the literature based on a broad variety of methodologies and forcings are 63.2 × 10 3 km 3 (Zhang et al, 2016), 65.0 × 10 3 km 3 (Jung et al, 2010), 65.5 × 10 3 km 3 (Oki and Kanae, 2006), 65.8 × 10 3 km 3 (Schlosser and Gao, 2010), 67.9 × 10 3 km 3 (Miralles et al, 2011a), 71 × 10 3 km 3 (Baumgartner and Reichel, 1975), 73.9 × 10 3 km 3 (Wang-Erlandsson et al, 2014), and 74.3 × 10 3 km 3 (Zhang et al, 2015). We note again that some of these studies considered the poles and desert regions, while others did not.…”
Section: Global Magnitude Of Terrestrial Evaporationmentioning
confidence: 99%
See 2 more Smart Citations
“…2); however, the contribution from these areas to the global volumes is rather marginal (< 5 % based on our analyses). For comparison, values typically found in the literature based on a broad variety of methodologies and forcings are 63.2 × 10 3 km 3 (Zhang et al, 2016), 65.0 × 10 3 km 3 (Jung et al, 2010), 65.5 × 10 3 km 3 (Oki and Kanae, 2006), 65.8 × 10 3 km 3 (Schlosser and Gao, 2010), 67.9 × 10 3 km 3 (Miralles et al, 2011a), 71 × 10 3 km 3 (Baumgartner and Reichel, 1975), 73.9 × 10 3 km 3 (Wang-Erlandsson et al, 2014), and 74.3 × 10 3 km 3 (Zhang et al, 2015). We note again that some of these studies considered the poles and desert regions, while others did not.…”
Section: Global Magnitude Of Terrestrial Evaporationmentioning
confidence: 99%
“…The global contribution of transpiration to total average evaporation has been extensively debated recently (Schlesinger and Jasechko, 2014;. Studies have reported values ranging between 35 and 90 %, based on isotopes (Jasechko et al, 2013;Coenders-Gerrits et al, 2015), sapflow measurements (Moran et al, 2009), satellite data (Miralles et al, 2011a;Mu et al, 2011;Zhang et al, 2016), and modelling (Wang-Erlandsson et al, 2014). Consequently, this large range of uncertainty is also expected in the relative contribution from other evaporation sources.…”
Section: Partitioning Of Evaporation Into Separate Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar zonal mean temporal pattern is found in transpiration in the STEAM (Simple Terrestrial Evaporation to Atmosphere Model) land surface model (Fig. 6 of Wang-Erlandsson et al, 2014). Because this model was evaluated using ERA-Interim forcing data, the high ET anomalies that we see in Fig.…”
Section: Evaluation Of Evapotranspiration and Runoffmentioning
confidence: 56%
“…This approximation is supported by the conservative nature of the ratio of mitochondrial respiration to gross photosynthesis and (hence) of the ratio of net photosynthesis to gross photosynthesis over a wide variety of conditions, on timescales of weeks or more (see the brief review in Van Oijen et al, 2010). Since each model time step in SEDGES is much shorter than this, it thus might seem incorrect to hold NPP / GPP fixed for each time step.…”
Section: Net Primary Productivity and Gross Primary Productivitymentioning
confidence: 97%